IMPLEMENTASI 4C DI ERA ABAD 21 DALAM PEMBELAJARAN TEMATIK INEGRATIF PADA GURU –GURU SD MOJOSONGO III SURAKARTA - Handini, Oktiana; Mustofa, Mukhlis (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2020)
This community service is in the form of delivering material exposure to the Implementation of 4C in the 21st Century Era in Integrative Thematic Learning to Teachers of SD Mojosongo III Surakarta. Community service by presenting teachers, school principals and in material presentation and interactive question and answer events to the level of mastery of SD Mojosongo III Surakarta teachers regarding the Implementation of 4C in the 21st Century Era in Integrative Thematic Learning for SD Mojosongo III Surakarta Teachers is intended to be able understand the essence of 4C in learning to support the smoothness of the learning process as well as theoretical clarity and a better understanding of learning, learning objects and learning situations and conditions in elementary schools. The delivery of this material to all teachers at SD Mojosongo III Surakarta, school principals and school supervisors totaling 25 teachers, both classroom and sports teachers, religion teachers and art teachers from parallel classes at the school. With the hope of teachers in the learning process in the classroom so that aspects of teacher knowledge and skills can further improve the abilities and professionalism of primary school teachers. Providing a scientific basis for elementary school teachers in understanding the essence of 4C Implementation in the 21st Century Era in Integrative Thematic Learning which consists of Communication, Collaboration, Critical Thinking and Creativity, and provide theoretical clarity and understanding better about learning, learning objects and learning situations and conditions in Primary Schools. The implementation will be held on Monday, July 15 2020 in the SD Mojosongo III Surakarta classroom with a 6 hour implementation time pattern, starting at 8.00 WIB until 15.00 WIB. The objectives of this community service are (1). Provide a scientific basis for elementary school teachers in understanding learning in the 21st Century Era in Integrative Thematic Learning (2). Provide theoretical clarity and better understanding of 4C communication, collaboration, critical thinking, creativity in learning in the 21st Century Era Keywords: 4C in the 21st century, communication, collaboration, critical thinking,